Tighter Analysis of an Approximation for the Cumulative VRP - Mulati, Mauro Henrique; Miyazawa, Flávio Keidi (Anais do Encontro de Teoria da Computação (ETC), 2017)
We deal with the cumulative vehicle routing problem (VRP), a generalization of the capacitated VRP, which objective is to minimize the fuel consumption. Gaur et al. in 2013 gave a 4-approximation based on a well-known partition heuristic to the traveling salesperson problem (TSP). We present a tighter analysis obtaining a (4 - 4/(3s 3 Q 2 ))-approximation, where Q is the capacity of the vehicle and s is a scaling factor. To the best of our knowledge, this is the best proved approximation for the cumulative VRP so far.